Study of lymphatic mapping and sentinel node identification in early stage cervical cancer - Rob, Lukas; Strnad, Pavel; Robova, Helena; Charvat, Martin; Pluta, Marek; Schlegerova, Dana; Hrehorcak, Martin (Gynecologic oncology, 2005)
OBJECTIVE: The aim of our study was to compare the identification of sentinel lymph nodes (SLN) by blue dye and (99m) Tc; to evaluate detection rate per patient and specific side detection rate (SSDR) of SLN, distribution of SLN and distribution of positive SLN and false negative rate of the methods. PATIENTS AND METHODS: From February 2000 until September 2004, we included 183 women with early stage cervical carcinoma. We evaluated two methods of detection of SLN (100 cases by Patent blue, 83 cases by Patent blue with (99m)Tc). We stratified the group upon the size of the tumor and upon the type of surgical method (laparoscopy, laparotomy). RESULTS: SLN identification increased in cases when we used combination of both methods (Tc + blue dye) SSDR = 93% versus the use of blue dye only SSDR = 71% (OR:5,76, CI 95% -2.9 -11.4, <0.0001). Distribution of 462 SLN-45.0% external iliac artery and vein, 42.6% supraobturator, 4.8 bifurcation and common illiac artery and vein, 4.6% praesacral, 3% medial part of lateral parametrium. Distribution of 44 positive SLN-approximately 38.6% external illiac artery and vein, 45.5% supraobturator, 6.8% bifurcation and common illiac artery and vein, 4.5% praesacral, 4.5% medial part of lateral parametrium. One false negative SN was in presacral area. CONCLUSION: Detection of SLN by combination of (99m)Tc and blue dye was statistically significantly better than blue dye alone. Our study documents high sensitivity, specificity and low false negativity of the method.
Keywords: Coloring Agents; False Negative Reactions; Humans; lidé středního věku; Female; Aged; falešně negativní reakce; dospělí; nádory děložního čípku; senioři; lidé; Lymphatic Metastasis; rosanilinová barviva; lymfatické metastázy; Rosaniline Dyes; biopsie sentinelové lymfatické uzliny; Adult; technecium 99mTc-agregovaný albumin; Lymph Nodes; staging nádorů; lymfatické uzliny; ženské pohlaví; Sentinel Lymph Node Biopsy; Middle Aged; barvicí látky; Radionuclide Imaging; Technetium Tc 99m Aggregated Albumin; Uterine Cervical Neoplasms; Neoplasm Staging; radiofarmaka; radioisotopová scintigrafie; Radiopharmaceuticals